Cognitive outcome after ventral capsule/ventral striatum stimulation for treatment-resistant major depression. Issue 3 (22nd September 2016) - Kubu, Cynthia S; Brelje, Tim; Butters, Meryl A; Deckersbach, Thilo; Malloy, Paul; Moberg, Paul; Tröster, Alexander I; Williamson, Eric; Baltuch, Gordon H; Bhati, Mahendra T; Carpenter, Linda L; Dougherty, Darin D; et al.
Abstract : Background: We report the neuropsychological outcome of 25 patients with treatment-resistant major depressive disorder (TRD) who participated in an Institutional Review Board (IRB)-approved randomised double-blind trial comparing active to sham deep brain stimulation (DBS) in the anterior limb of the ventral capsule/ventral striatum (VC/VS). Methods: Participants were randomised to active (n=12) versus sham (n=13) DBS for 16 weeks. Data were analysed at the individual and group levels. Group differences were analysed using repeated measures ANOVAs. Relationships between depression severity and cognition were examined using partial correlations. The false discovery rate method controlled for multiple analyses. Results: No significant interactions comparing active versus sham stimulation over time were evident. Change in depression was unrelated to change in neuropsychological measures. Twenty patients declined by ≥1 SD on at least one measure (41.3% of declines occurred in active group participants; 63.0% in older participants regardless of stimulation status). Twenty-two patients exhibited improvements >1 SD on neuropsychological measures (47.7% in the active group; 63.1% in younger participants). Conclusions: These data suggest that VC/VS DBS in patients with TRD does not significantly affect neuropsychological function. Age at surgery, regardless of stimulation status, may be related to cognitive outcome at the individual patient level. Trial registration number: NCT00837486 ; Results.